Validity of Addendums which Made Under Hands Due to a Default on Cooperation Agreement Deed - Lely Yuliana; Jawade Hafidz; Ira Alia Maerani (Sultan Agung Notary Law Review, 2022)
This writing aims to find out and analyze the validity of the addendum made by the parties under the hand due to the occurrence of default of the cooperation agreement deed made before a Notary and to know and analyze the legal considerations by the judge in deciding the case number 15/Pdt.G/2016/PN.Kds. This research method uses a normative juridical approach, which is an approach using secondary data as the main data. Secondary data is data obtained by conducting library research. The results of this study indicate that basically in an agreement it is allowed to add an addendum on the condition that the parties agree, this is because in the addition of an addendum to add, changing or eliminating something in the agreement is always related to the main agreement, as stipulated in Article 1320 of the Civil Code regarding the conditions for the validity of the agreement. The main key to an addendum is the agreement of the parties in accordance with Article 1320 of the Civil Code.